EXPLORING CAREER ANCHORS OF TAIWANESE DIGITAL NOMADS: PERSPECTIVE OF GEN Z AND MILLENNIALS - Kah Xin, Chia (PEOPLE: International Journal of Social Sciences, 2025)
With the advancement of technology and the widespread adoption of remote work, career paths and work styles have become increasingly diverse. Particularly after the COVID-19 pandemic, more individuals are engaging in location-independent work, blurring the boundaries between work, life, and place. While existing literature in Western contexts has extensively examined the motivations, identities, and challenges of digital nomads, research from non-Western societies remains scarce. To address this gap, this study investigates the career anchors of Taiwanese Gen Z and Millennial digital nomads through a literature review and a questionnaire survey based on Edgar H. Schein’s career anchors (Schein, n.d.). Preliminary findings indicate that “autonomy” and “lifestyle” emerge as dominant career anchors among the respondents. This suggests a shift away from traditional work values toward self-directed, mobility-driven career paths. The study aims to contribute a non-eastern perspective to the global understanding of lifestyle-based career models. Future research will include qualitative interviews and may provide actionable insights for employers, policymakers, and support organizations to better address the evolving needs and well-being of this emerging workforce.